2012
DOI: 10.5552/drind.2012.1207
|View full text |Cite
|
Sign up to set email alerts
|

Neka fizikalna i mehanička svojstva drva šljive (Prunus Domestica L.)

Abstract: Neka fizikalna i mehani~ka svojstva drva {ljive (Prunus Domestica L.) Some Physical and Mechanical Properties of Plum Tree (Prunus Domestica L.) Prispjelo -received: 27. 2. 2012. Prihvaćeno -accepted: 15. 11. 2012 674.031.734.4 doi:10.5552/drind.2012 Stručni rad • Professional paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…These results indicated that the zone of the juvenile wood from the aspect of the oven-dry density spreads up to the 60 th annual ring from pith to bark. This conclusion does not correspond to the results found in literature (Govorčin et al 1998;Zobel and Sprague 1998;Koubaa et al 2005;Alteyrac et al 2006;Mvolo et al 2015;Sedlar et al 2019) Bending strength is one of the most important mechanical properties of wood that determines the usefulness of wood, especially from the aspect of the position of wood from pith to bark. The differences in the static bending strength values from pith to bark are significant.…”
Section: Fig 2 Distribution Of Oven-dry Density In the Radial Directi...contrasting
confidence: 57%
See 1 more Smart Citation
“…These results indicated that the zone of the juvenile wood from the aspect of the oven-dry density spreads up to the 60 th annual ring from pith to bark. This conclusion does not correspond to the results found in literature (Govorčin et al 1998;Zobel and Sprague 1998;Koubaa et al 2005;Alteyrac et al 2006;Mvolo et al 2015;Sedlar et al 2019) Bending strength is one of the most important mechanical properties of wood that determines the usefulness of wood, especially from the aspect of the position of wood from pith to bark. The differences in the static bending strength values from pith to bark are significant.…”
Section: Fig 2 Distribution Of Oven-dry Density In the Radial Directi...contrasting
confidence: 57%
“…The difference in the results of these two types of research samples is substantial, and it can influence the variability of the obtained results. In analyzing the samples from trees to obtain the distribution of properties in the radial direction, the variability of the results will be significantly greater because of the nature of forming wood cells in the tree in the radial direction (Govorčin et al 1998(Govorčin et al , 2003. Therefore, it is necessary to consider the juvenile, mature, and overmature phases of tree growth.…”
Section: Introductionmentioning
confidence: 99%
“…These species were evidenced to have good wood hardness, strength, and elasticity properties. For example, Grewia bicolor and O. europaea have good wood hardness, strength, and specific weight, which make them well-placed for traditional plowing implements and hence ideal candidates for agricultural farming equipment (Govorčin et al 2010;Ruffo et al 2002).…”
Section: Farm Implementsmentioning
confidence: 99%